DESAIN PENAIK TEGANGAN MENGGUNAKAN KOMBINASI KY DAN BUCK-BOOST CONVERTER PADA SISTEM PHOTOVOLTAIC - Soedibyo Soedibyo; Antonius Rajagukguk (SENTIA 2016, 2016)
today's development, needs the use of renewable energy sources (renewable energy) is increasingly important. Because renewable energy can be used as a source of energy, used to generate the primary generating system and energy source supporting the main plant. One of the renewable energy used for the generation system is the energy of the sun using photovoltaic (PV). When happen the light intensity change, the resulting DC current out put of PV, also fluctuations. Therefore, needed a device of technology capable of raising the voltage if the light intensity decreases, with use DC to DC converters. In this study, designed and implemented the DC to DC converter topologies, hybrid KY and buck-boost converter, that is used to increase the DC voltage generated by the PV. The implementation results show the converter can work at different voltage ranges enter and have a voltage conversion ratio reached 7.16 times with 81.18% efficiency at 90% load power.